2015
DOI: 10.1007/s11606-015-3501-5
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Continuation of Medications Intended for Acute Illness After Hospital Discharge: A Population-Based Cohort Study

Abstract: BACKGROUND:Patients are vulnerable to medicationrelated errors during transitions in care. Patients discharged from acute care hospitals may be at an elevated risk for the unintentional continuation of medications prescribed to prevent or treat complications that are associated with acute illness but are no longer indicated. We sought to evaluate rates of (primary objective) and risk factors for (secondary objective) potentially unintentional medication continuation following hospitalization. METHODS: A popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 31 publications
(32 reference statements)
5
60
0
Order By: Relevance
“…Antipsychotics are not the only class of medications that are prescribed at discharge despite being no longer indicated at that time. Scales and colleagues [31] examined four medication classes, for example, and found that all four were prescribed at hospital discharge without a documented indication. We specifically focused on antipsychotics in the current study because, unlike some medications (e.g., gastric acid suppressants), antipsychotics have never been proven efficacious in the ICU setting and their adverse effects during chronic use are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics are not the only class of medications that are prescribed at discharge despite being no longer indicated at that time. Scales and colleagues [31] examined four medication classes, for example, and found that all four were prescribed at hospital discharge without a documented indication. We specifically focused on antipsychotics in the current study because, unlike some medications (e.g., gastric acid suppressants), antipsychotics have never been proven efficacious in the ICU setting and their adverse effects during chronic use are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…There are many instances where patients intentionally altering their medications may be beneficial. For example, large number of patients are prescribed a gastric acid suppressant intended for short‐term use, which may be continued long term without review . If patients themselves identify that a medication is unnecessary where the doctor has failed to do so, then this is likely to be a positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, large number of patients are prescribed a gastric acid suppressant intended for short-term use, which may be continued long term without review. 23 If patients themselves identify that a medication is unnecessary where the doctor has failed to do so, then this is likely to be a positive outcome. Ideally, it should prompt discussion with their physician and regular review of their medications, rather than self-management of medications.…”
Section: Reasons For Intentional Non-adherencementioning
confidence: 99%
“…Medications typically intended for short-term use during acute illness are sometimes continued after discharge without a documented indication [ 47 ]. While it is possible that these drugs were appropriately started during an acute illness in the ICU, most should have been discontinued at ICU or hospital discharge [ 48 ].…”
Section: Medications: a Special Concern In Old Patientsmentioning
confidence: 99%